Persepsi Mahasiswa Ilmu Komputer atas Penggunaan AI dalam Karya Ilmiah Berbahasa Indonesia - Nazwa Salsyabilla Ramadhani; Juliana Gloria Br Sipayung; Maria Winarni Br Silitonga; Nuriana Sipahutar (CV. ITTC INDONESIA, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought significant changes to the academic world, including in the process of scientific writing. This study aims to examine the perceptions of Computer Science students at Universitas Negeri Medan (UNIMED), Class of 2024, toward the use of AI in writing Indonesian-language scientific papers. The distinctive aspect of this study lies in its focus on Indonesian as the medium of academic writing, which presents unique linguistic challenges that differ from AI use in English-language academic contexts. The study employs a quantitative approach with a descriptive survey design. Data were collected through an online questionnaire distributed via Google Form to students in Classes A, B, C, and D. The research instrument covers six aspects: knowledge and understanding, attitudes toward AI, experience and behavior, perceived benefits, academic ethics and integrity, and expectations and regulation. The findings are expected to provide a comprehensive picture of computer science students’ perceptions of AI use and serve as a basis for relevant academic policy-making.